2017
DOI: 10.1002/bab.1559
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of horseradish peroxidase on ZnO nanowires/macroporous SiO2 composites for the complete decolorization of anthraquinone dyes

Abstract: A zinc oxide (ZnO) nanowires/macroporous silicon dioxide composite was used as support to immobilize horseradish peroxidase (HRP) simply by in situ cross-linking method. As cross-linker was adsorbed on the surface of ZnO nanowires, the cross-linked HRP was quite different from the traditional cross-linking enzyme aggregates on both structure and catalytic performance. Among three epoxy compounds, diethylene glycol diglycidyl ether (DDE) was the best cross-linker, with which the loading amount of HRP with pI of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Many researchers have also used horseradish peroxide (HRP) in the degradation of organic dyes. For example, Sun et al [61] researched the immobilization of horseradish peroxidase on silica coated with zinc oxide. The results indicated that the proposed catalyst HRP/ZnO/SiO 2 exhibited a high decolorization efficiency and good reusability for anthraquinone dyes.…”
Section: Organic Dyesmentioning
confidence: 99%
“…Many researchers have also used horseradish peroxide (HRP) in the degradation of organic dyes. For example, Sun et al [61] researched the immobilization of horseradish peroxidase on silica coated with zinc oxide. The results indicated that the proposed catalyst HRP/ZnO/SiO 2 exhibited a high decolorization efficiency and good reusability for anthraquinone dyes.…”
Section: Organic Dyesmentioning
confidence: 99%
“…[39][40][41][42] More recently, ZnO nanowires were found to be capable of adsorbing bi-epoxy compound (diethylene glycol diglycidyl ether, DDE) that can react with amino groups on HRP; thus, an in situ cross-linking of HRP molecules was realized on the surface of ZnO nanowires. 43,44 This was quite different from the traditional method of CLEA preparation, in such a case the size of CLEAs of HRP could be limited because the amount and distribution of cross-linker was controlled by the structure of the nano-composite support.…”
Section: Introductionmentioning
confidence: 97%
“…ZnO and TiO 2 have been widely used as supports for enzyme immobilization [30][31][32][33]. For example, Movahedi et al [34] developed an easy and effective method of increasing the stability of lactoperoxidase (LPO) immobilized on ZnO nanoparticles (ZnO/LPO).…”
Section: Introductionmentioning
confidence: 99%